Pengaruh Alokasi Anggaran Pendapatan dan Belanja Daerah Dalam Meningkatkan Kesejahteraan Masyarakat Di Kabupaten Sidoarjo - Izza, Mohammad Alfin Syaiful; Sitohang, Arga Christian (widya balina, 2024)
The Regional Revenue and Expenditure Budget (APBD) is the annual financial plan of regional governments in Indonesia which is approved by the Regional People's Representative Council. And also the main policy instrument for regional governments which is used as a tool to determine the amount of income and expenditure. In Sidoarjo Regency, the effectiveness of APBD management is an important factor in accelerating regional development, reducing poverty and improving the quality of life of the community. Therefore, appropriate and effective APBD distribution is very important in promoting sustainable community welfare. This research uses quantitative methods. This research uses multiple linear regression analysis. The results of this research are based on the results of simultaneous tests for the variables of effectiveness of APBD allocation and efficiency of APBD allocation on community welfare in Sidoarjo Regency, obtained an F-count of 22.995 with a significance of 0.015. The significance level is smaller than 0.05, which means that H0 is rejected and Ha is accepted. In this study, the hypothesis of the variable effectiveness of APBD allocation (X1) shows that the t-count value is -3.394 with a significance of 0.043 which is smaller than 0.05. Thus H0 is rejected and H2 is accepted. In this research, the hypothesis test shows that the variable APBD Allocation Efficiency (X2) shows that the t-value is 4.714 with a significance of 0.018 which is smaller than 0.05. Thus H0 is rejected and H3 is accepted.